2007
DOI: 10.1007/s10903-007-9084-4
|View full text |Cite
|
Sign up to set email alerts
|

Results from a Community-based Occupational Health Survey of Vietnamese-American Nail Salon Workers

Abstract: A community-university collaborative partnership assessed self-reported work-related health effects and environmental factors in Boston's Vietnamese immigrant community via an interviewer-assisted survey. Seventy-one nail technicians responded. Musculoskeletal disorders, skin problems, respiratory irritation and headaches were commonly reported as work-related, as were poor air quality, dusts and offensive odors. The reporting of a work-related respiratory symptom was significantly associated with the reportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
81
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 16 publications
9
81
0
Order By: Relevance
“…Exposures to the types of chemicals in nail products-organic solvents, formaldehyde, and acrylic compounds-and low ventilation rates have both been associated with the symptoms reported in our survey [19,20]. Because a previous study had found that nail salon owners and staff were often not able to correctly describe the air handling devices in their salons, ventilation and other exposure metrics were assessed through a salon audit conducted by a trained researcher [7]. In addition to metrics relating to the volume of chemical use and the number of exposed individuals, the audit focused on gaining an understanding of the adequacy of fresh air in salons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposures to the types of chemicals in nail products-organic solvents, formaldehyde, and acrylic compounds-and low ventilation rates have both been associated with the symptoms reported in our survey [19,20]. Because a previous study had found that nail salon owners and staff were often not able to correctly describe the air handling devices in their salons, ventilation and other exposure metrics were assessed through a salon audit conducted by a trained researcher [7]. In addition to metrics relating to the volume of chemical use and the number of exposed individuals, the audit focused on gaining an understanding of the adequacy of fresh air in salons.…”
Section: Introductionmentioning
confidence: 99%
“…While salon chemical concentrations are unlikely to exceed established exposure limits, work-related health complaints by nail salon workers are common. One survey of Boston area nail technicians found that self-reported work-related health symptoms such as skin and respiratory irritation, difficulty breathing, headaches, and trouble concentrating were reported by significant percentages of the workers surveyed (see Table 3) [7]. Additionally, the workers reported high levels of concern about chemical exposures at work and almost universal (voluntary) use of masks.…”
Section: Introductionmentioning
confidence: 99%
“…Denmark [19][20][21][22][23], Finland [24,25], the Netherlands [26] and the USA [27,28]. With the German version of the NOSQ-2002, the collection of standardized data on this important occupational disease will be possible in Germany as well.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the number of nail technicians registered in the US has increased by over 340% since 1991, reaching almost 400 000 in 2005 (1). According to estimates of the Central Statistical Office, in Poland there are currently >100 000 registered nail technicians (unpublished data).…”
mentioning
confidence: 99%
“…Recent studies have indeed reported that occupational exposure to chemical products used in the nail industry may be associated with various adverse health effects including skin, eyes, and upper-airways mucosa irritation, headaches, musculoskeletal and reproductive system disorders, and asthma (1,(27)(28)(29)(30)(31)(32). Nevertheless, not much is known about how such exposure affects the levels of biochemical markers among nail technicians.…”
mentioning
confidence: 99%